Setophoma aseptata sp. nov. and new record of Minutisphaera aspera from Yuanjiang River Basin, China - Cai, Yuan-Ting; Zhang, Liang; Shen, Hong-Wei; Bao, Dan-Feng; Luo, Zong-Long (Phytotaxa, 2025)
During an investigation into the diversity of lignicolous freshwater fungi in the Yuanjiang River Basin of Yunnan Province, China, a new species named Setophoma aseptata and a new geographical record, Minutisphaera aspera, were discovered and described based on morphology and phylogenetic ecidence. Setophoma aseptata forms an independent clade in the phylogenetic analysis of combined ITS and LSU gene regions. Morphologically, Setophoma aseptata is characterized by globose to subglobose conidiomata with relatively thick conidiomatal walls, cylindric- clavate to ampulliform conidiogenous cells, and hyaline, ovoid or ellipsoidal, aseptate conidia. Detailed descriptions, illustrations, and phylogenetic trees for these species are provided in the study.